Strategy of School Principals in Creating Effective Learning During Pandemic - Irawan, Nandi; Lian, Bukman; Mahasir, Mahasir (Journal of Social Work and Science Education, 2023)
This study aims to identify and analyze: (1) Principal’s strategy during the Covid-19 pandemic in realizing effective learning at SMP Negeri 8 Rambang Kuang; (2) Implementation of learning during the Covid-19 Pandemic at SMP Negeri 8 Rambang Kuang; (3) Supervision of learning implementation during the Covid-19 pandemic at SMP Negeri 8 Rambang Kuang. This is qualitative research with descriptive method. This research was conducted at SMP Negeri 8 Rambang Kuang. Data collection techniques were carried out by observation, interviews, documentation, and literature studies. The validity of the data was tested by triangulation. The results of the study show that the principal’s strategy to realize effective learning is carried out by optimizing support facilities for online teaching and learning activities, and also increasing a sense of security and comfort for all school residents from the threat of the spread of the covid-19 virus by completing the facilities and infrastructure to prevent the transmission of the covid-19. Online learning still experiences many obstacles, such as when the lights go out, the internet signal is lost, the data quota is expensive, students spend a lot of their daily time playing instead of studying, the lack of interaction between teachers and students has an impact on the decline in the character values ​​of students. To ensure the online learning process is carried out properly, the principal continues to directly supervise and evaluate any obstacles that occur.